Phenotype and outcomes of very early onset and early onset inflammatory bowel diseases in a Montreal pediatric cohort - Chapuy, Laurence; Leduc, Bertrand; Godin, David; Damphousse, Amélie; Patey, Nathalie; Dal Soglio, Dorothee; Jantchou, Prevost; Deslandres, Colette (Frontiers in Pediatrics, 2023)
Objectives The incidence of very-early-onset inflammatory bowel disease (VEO-IBD) and early-onset IBD (EO-IBD) is increasing. Here, we report their phenotype and outcomes in a Montreal pediatric cohort. Methods We analyzed data from patients diagnosed with IBD between January 2014 and December 2018 from the CHU Sainte-Justine. The primary endpoint was to compare the phenotypes of VEO-IBD and EO-IBD. The secondary endpoints involved comparing outcomes and rates of steroid-free clinical remission (SFCR) at 12 (±2) months (m) post-diagnosis and at last follow-up. Results 28 (14 males) and 67 (34 males) patients were diagnosed with VEO-IBD and EO-IBD, respectively. Crohn's disease (CD) was more prevalent in EO-IBD (64.2% vs. 39.3%), whereas unclassified colitis (IBD-U) was diagnosed in 28.6% of VEO-IBD vs. 10.4% of EO-IBD (p < 0.03). Ulcerative colitis (UC) and IBD-U predominantly presented as pancolitis in both groups (VEO-IBD: 76.5% vs. EO-IBD: 70.8%). Combining all disease subtypes, histological upper GI lesions were found in 57.2% of VEO-IBD vs. 83.6% of EO-IBD (p < 0.009). In each subtype, no differential histological signature (activity, eosinophils, apoptotic bodies, granulomas) was observed between both groups. At 12 m post-diagnosis, 60.8% of VEO-IBD and 62.7% of EO-IBD patients were in SFCR. At a median follow-up of 56 m, SFCR was observed in 85.7% of VEO-IBD vs. 85.0% of EO-IBD patients. Conclusion The rate of patients in SFCR at 1-year post-diagnosis and at the end of follow-up did not significantly differ between both groups.